The Influence Of Organizational Culture And Organizational Commitment On Employee Engagement And Its Implications On Doctor Performance - Catur Setiya Sulistiyana; Purwadi Purwadi; Rian Andriani (Jurnal Medisci, 2026)
Background. Education at the professional stage provides the opportunity to practice several important skills, such as anamnesis, physical examination, clinical reasoning, decision-making, empathy, and professionalism, in an integrated manner. This aims to improve student competence by participating directly in the health service process, such as interacting with patients, observing doctors, understanding cases, and independent learningAims. This study aims to examine the impact of organizational culture and commitment on employee engagement and its effects on the performance of clinical educators at the teaching hospitals of the Faculty of Medicine, Swadaya Gunung Jati University. Methods. The research method employed is a quantitative descriptive approach with an explanatory research design. Data were collected using a questionnaire employing a Likert scale, involving 92 respondents selected using the Slovin formula. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 3. Result. The study's findings indicate that corporate culture and organizational commitment positively and significantly influence employee engagement. Moreover, company culture, organizational commitment, and employee engagement exert a favorable and significant influence on the effectiveness of clinician educators. Employee engagement has been shown to mediate the relationship between organizational culture and organizational commitment and to partially enhance the impact of these factors on the performance of clinicians and educators. Conclusion. The findings suggest that enhancing organizational culture and bolstering organizational commitment can foster clinician-educator physicians' engagement, thereby positively influencing performance in education, service, research, and community outreach. This research aims to provide a foundation for teaching hospital management and for developing sustainable human resource management techniques